Pattern of Serum High Density Lipoprotein (Hdl) & Low Density Lipoprotein (Ldl) Level In Hypertensive Patient (Journal of Dhaka Medical College, 2023)
Background: Hypertension and dyslipidemia are major risk factors for cardiovascular disease, accounting for the highest morbidity and mortality among the Bangladeshi population. The aim of our study is to determine the pattern of serum Low Density and High Density Lipoprotein level in hypertensive patient. Methods: This observational cross sectional study was carried out among100 patient admitted in Department of Medicine in Dhaka Medical College Hospital. Patients were enrolled consecutively and informed written consent was obtained. Detailed information wererecorded in questionnaire approved by the ethical review committee of Dhaka Medical College.Results: Among 100 cases, the mean age was found 48.76±7.11 years in hypertensive group and 38.39±8.41 years in normotensive group. Mean total cholesterol was found 239.43±22.17 mg/dl in hypertensive group and 189.21±14.26 mg/dl in normotensive group. Mean triglyceride was 178.34±10.94 mg/dl in hypertensive group and 142.48±12.83 mg/dl in normotensive group. Mean HDl-cholesterol was 39.24±5.07 mg/dl and 44.28±7.82 mg/dl in hypertensive and normotensive group respectively. Mean LDL-cholesterol was 154.78±13.55 mg/dl in hypertensive group and 116.72±12.33 mg/dl in normotensive group. Binary logistic regression analysis showed high Total Cholesterol was significantly associated with hypertensive patients and the odds ratio (OR) was 1.21, 95% CI 0.97–1.67, P